Impact of Prolonged Skeletal Traction in Patients With Acetabular Fractures. Issue 2 (February 2020) - Boissonneault, Adam R.; Schenker, Mara; Wilson, Jake; Schwartz, Andrew; Staley, Christopher; Maceroli, Michael
Abstract : Objectives: To explore the association between increased time in traction and in-hospital pulmonary complications in patients with acetabular fractures. Design: Retrospective. Setting: Level I trauma center. Patients/Participants: One hundred ninety consecutive patients. Intervention: Application of skeletal traction before fixation of acetabular fracture. Main Outcome Measurements: The primary outcome measure was pulmonary complication as defined by pulmonary embolism, pneumonia, and acute respiratory distress syndrome. Secondary outcome measures included length of intensive care unit stay (in days), total length of hospital stay (in days), deep hardware-associated infection, subsequent conversion to total hip arthroplasty, urinary tract infection, and lower-extremity deep venous thrombosis. Results: The mean time in traction for patients who developed a pulmonary complication was 210 hours compared with 62 hours for those who did not ( P < 0.001). After controlling for Injury Severity Score, chest injury, and concomitant long bone injury requiring intramedullary nailing, the odds of developing a pulmonary complication for patients who spent longer than 120 hours in traction were over 40 times higher than those treated within 5 days ( P < 0.001). The mean intensive care unit stay for patients who spent at least 120 hours in traction was 17 days compared with 5 days for those treated in less than 120 hours ( P < 0.001). Conclusion: Early definitive fixation and decreased time in skeletal traction is associated with a lower rate of complications in patients with acetabular fractures. Our results would suggest that fixation of acetabular fractures before 120 hours (5 days) confers a significant risk-reduction benefit. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.